Basic income on the agenda : policy objectives and political chances - Veen, Robert van der; Groot, L. F. M. (Lucas Franciscus Michaël), 1962- (Amsterdam University Press ; Eurospan, 2000)
A inquiry into the pros and cons of an unconditional basic income.
Keywords: Minimum wage -- Europe.; Income maintenance programs.; Basic income.; Basic income -- Government policy -- Europe.; Income maintenance programs -- Government policy -- Europe.; Sécurité du revenu.; Sécurité du revenu -- Politique gouvernementale -- Europe.; Revenu annuel garanti.; Revenu annuel garanti -- Politique gouvernementale -- Europe.; Salaires minimums -- Europe.; Society and culture: general.; SOCIAL SCIENCE -- Poverty & Homelessness.; POLITICAL SCIENCE -- Comparative Politics.; Income maintenance programs; Basic income -- Government policy; Basic income; Minimum wage; Europe; Mindestlohn; Europa; Basisinkomen.; Overheidsbeleid.; Amsterdam <2000>; Sociology: work and labour.; Labour / income economics.; Welfare economics.; Electronic books.